Waste-derived volatile fatty acid production and ammonium removal from it by ion exchange process with natural zeolite. Issue 6 (1st June 2022) - Sapmaz, Tugba; Mahboubi, Amir; Taher, Mustafa N.; Beler-Baykal, Bilsen; Karagunduz, Ahmet; Taherzadeh, Mohammad J.; Koseoglu-Imer, Derya Y.
ABSTRACT: Volatile fatty acids (VFAs) produced during anaerobic digestion (AD) of organic waste are a promising alternative carbon source for various biological processes; however, their applications are limited due to the presence of impurities such as ammonium (NH4 + ). This study investigates the potential for removal of ammonium using a naturally occurring zeolite (clinoptilolite) from chicken manure (CKM) derived VFA effluent recovered from an anaerobic membrane bioreactor (MBR). Experiments were conducted for both synthetic and actual VFA (AD-VFA) solutions, and the effects of different parameters were investigated with batch and continuous studies. It was observed that the Langmuir-type isotherm provided the best fit to the equilibrium data in the isotherm investigations carried out with the AD-VFA solution. The maximum adsorption capacity (qm ) was found as 15.7 mg NH4 + /g clinoptilolite. The effect of some operational parameters on process performance such as pH, initial NH4 + loading and potassium ion (K + ) concentration was investigated. The pH had a negligible effect on ammonium removal for a pH range of 3–7, while the removal efficiency of ammonium decreased with the increase of initial NH4 + loading and K + concentration. At the optimum conditions determined in batch experiments, the ammonium removal from synthetic and AD-VFA solutions were compared and average ammonium removal efficiencies of 93 and 94% were found in 12 h equilibrium time for synthetic and AD-VFA solutions, respectively. Overall findings indicated that clinoptilolite has excellent potential for ion exchange when combined with biological processes such as acidogenic fermentation of VFAs to purify the solution from high-ammonium content. GRAPHICAL ABSTRACT: uf0001